Economic Comparison between Pasture-Based Beef Production and Afforestation of Abandoned Land in Swedish Forest Districts - Karl-Ivar Kumm; Anna Hessle (Land, 2020)
Large areas of agricultural land have been abandoned or are at risk of being abandoned such as small scattered fields and pastures in forest-dominated landscapes are unsuitable for modern mechanized agriculture and cost-efficient grazing. These areas have therefore become unprofitable to cultivate and graze. Spruce planting has been seen as the obvious alternative on these lands but is today questioned from landscape points of view. Now most abandoned land is left for natural afforestation. This study aims to compare the profitability in use of abandoned or marginal agricultural land in Swedish forest districts for spruce planting, natural birch afforestation, or organic beef cattle grazing large pasture-forest mosaics. The pastures consist of remaining semi-natural pastures, abandoned and marginal agricultural land, and adjacent forest land. Calculations of contribution to land, management, and risk suggest that, given present supports and environmental payments, organic beef production with herds of more than 20 suckler cows in large pasture-forest mosaics could be more profitable than forestry, except for in the most fertile areas of southern Sweden, where spruce planting has the highest contribution. Future tree breeding progress and possible decrease of livestock-related support and environmental payments would however increase the competitiveness of resumed afforestation relative to beef production.